Code blue [large type] - Michaels, Fern (Michaels, Fern. Sisterhood, 2026)
"When a letter arrives telling Theresa Gallagher that her aunt is in a nursing home, Theresa flies out to see her. The staff at the Sunnydale Care Facility seem pleasant and efficient, but Theresa finds it strange that she's only permitted to "observe" her aunt from a viewing room. It's the first of several red flags that lead Theresa to start asking questions. Soon the Sisterhood is on the case, uncovering evidence that at Sunnydale, seniors are mistreated, duped, and drained of their savings. But no one is beyond justice--not when the Sisterhood's extraordinary women are involved, making wrongs right as only they can"--